Evaluation of Collections, Services and Identiyfing the Challenges in Providing Services of Public Libraries at Vali; East Pradeshiya Sabha of Jaffna, Sri Lanka - Sritharan, T. (Sri Lanaka Library Association, 2021)
The objective of this study was to evaluate the collection, services and identify the challenges in providing services of the public libraries in Vali -East Pradeshiya Sabha of Jaffna district, Northern Province, Sri Lanka_ There are five public libraries in Vali -East Pradeshiya Sabha. They are Achchuveli public library, Puttur Public library, Kopay Public Library, Neerveli Public library and Urumbirai Public library. Both quantitative and qualitative research methods were used as the research design. Questionnaires and interviews were used as research instruments to conduct this research. Questionnaires were distributed to a sample of 100 readers who averagely visit these public libraries in a month and all five librarians in-charges of these libraries were selected for the structured interview. The response rate for the questionnaire was 94% and among them 60% was female and 30% was male respondents. Among the respondents 50 (53.2%) of them were school and university students. The findings revealed that 58 (6L7%) of them visited the library to borrow books and 14 (14.9%) of them visited to study their own books. The respondents 39(41.5%) indicated that lending section was the most utilized section in these libraries when comparing with other sections, 54 (57.4%) of them were satisfied and 28 (29.8%) of them were dissatisfied with the services. Among 94 respondents 89 (94.7%) of them mentioned that they were aware of the services rendered by these libraries and 5 (5.3%) of them were not aware about the services. In addition, 63 (67%) respondents satisfied on collection available at these libraries and 92 (97.9%) of the respondents were satisfied with the services rendered by these libraries. According to the qualitative data, less training, inadequate staff, lack of technological instruments, inability to conduct library extension services and non-availability of proper library environment were identified as challenges in providing library services. The library services provided by these libraries to their community by using the government allocation and private donations were obvious. This study recommended that the allocation for these libraries should be increased, the environment of these libraries should be monitored and developed, technical instruments such as computers and photocopy machines should be provided in order to modernize the libraries and their facilities, In addition human resources and vehicles should be provided to enhance the library extension services.
Keywords: Public Library; Vali — East Pradeshiya Sabha Libraries; Library Collection; Library Services